National Security and Parliamentary Review Four Years On - David J. McGuinty (The Journal of Intelligence, Conflict and Warfare, 2021)
On July 15, 2021, the Canadian Association for Security and Intelligence Studies (CASIS) Vancouver hosted a digital roundtable titled National Security and Parliamentary Review Four Years On: Is it Working? The presentation was conducted by the Honourable David J. McGuinty, founding chair of the National Security and Intelligence Committee of Parliamentarians (NSICOP). The presentation was followed by a question and answer period with questions from the audience and CASIS Vancouver executives, which were directed to both Mr. McGuinty and Lisa Marie Inman, Executive Director, Secretariat of NSICOP.